Ragweed components in honey - Nagy, Éva; Novák, Anna; Daróczi, Lajos; Jávor, András (Acta Agraria Debreceniensis, 2017)
The aim of this research was to prove that the syrup containing ragweed used for feeding the bees was transferred to the honey. To reach this goal we developed a method to analyse the volatile components of the samples. We applied two sample preparation methods. The first one was SPME (Solid Phase Micro Extraction) preparation from the headspace of all of the samples. In the second case only the raw leaves of the ragweed were extracted with n-hexane and dichloromethane to complete the SPME results. The measurements were performed on GC-MS equipment. Chromatograms and data evolution showed that the components of the ragweed were also present in honey so they were transferred by bees.